Crecimiento de las plantas de Cedrelinga cateniformis Ducke con fertilización foliar en plantación. Puerto Almendra, Loreto, Peru-2021 - Rodriguez Perez, Rudi (2024)
The thesis was carried out in a CIEFOR Puerto Almendra - FCF - UNAP plantation, San Juan Bautista, Maynas, Loreto, Peru. The objective was to determine if the growth of Cedrelinga cateniformis Ducke “tornillo” plants varies with different concentrations of foliar fertilizer in plantation. In the trial, the factorial experiment arranged in a completely randomized block design was used where the fertilization dose with levels a0 = 20 ml was considered as factor “A”; a1 = 40 ml and a2 = 60 ml dissolved in 20 L of water and, as factor “B” to the frequency of fertilizer fumigation with levels b0 = 2 times per week and b1 = 3 times per week; with 3 repetitions. The results indicate that in treatment a0 b1 (20 ml of concentrate / 20 L of water with fumigation 3 times per week) the highest average height was obtained with 132,4 cm and in treatment a0 b0 (20 ml of concentrate / 20 L of water with fumigation 2 times a week) the largest diameter was 13,7 mm. In statistics, it was found that there is a significant difference between the dose levels of foliar fertilization; However, at the levels of Factor “B” and in the AxB Interaction there is no significant difference within them, with 95% confidence.